Alamat ng paniki The legend of the bat - Matias, Segundo D.; Madueño, Ghani ([Manila] Lampara Pub. House, 2010)
This modern legend will tell us why the bats come out of their lair only at night and why they hang uside down from their perch.
Stories with moral values
Text in Filipino and english.